UNCONVENTIONAL TECHNIQUE USED TO MANUFACTURE POROUS HIGH-STRENGTH GLASS FOAM - LUCIAN PAUNESCU; SORIN MIRCEA AXINTE; MARIUS FLORIN DRAGOESCU; BOGDAN VALENTIN PAUNESCU; FELICIA COSMULESCU (Journal of Engineering Studies and Research)
The paper presents experimental results obtained in the manufacturing process of porous high-strength glass foam for thermal insulation in buildings made of glass waste and kaolin clay as raw materials and dolomite as a foaming agent. The paper’s originality is the use of the unconventional microwave heating technique. The best product manufactured by this technique was that sintered at 1050 ºC using 18 wt.% kaolin clay and 3.5 wt.% dolomite. The product characteristics were: the apparent density of 0.66 g·cm-3, the thermal conductivity of 0.155 W/m·K, the compressive strength of 5.3 MPa and a microstructural homogeneity with pore size between 0.20-0.50 mm.